Audience response system utilization outcome in secondary school environment - Jonathan Mamangkian, Mantikayan; Abdullah, Lili Marziana; Montadzah Ambag, Abdulgani (2014)
It is not about the tools, it’s using the tools to facilitate learning. This research explores the nature of the outcomes experienced by students for using audience response system technology in the classroom. Specifically, this study answers the question “What are the impacts of ARS on performance outcomes in secondary level education?” A personally administer questionnaire and quasi-experimental method was used. Kirkpatrick’s four-level model was used to measure the performance outcome of the student in computer studies class at Adni International Islamic School. The finding shows that, student reaction outcome was positive. Student learning outcome improved but student behavior slightly changes due to the utilization of ARS. The post-test result outcome shows that there is no significant difference between students who received instruction through the audience response system and students who received instruction through non-technology based methods.